OVERLOOKING THE TRANSFORMATION OF VALUES THROUGH THE TRANSNATIONAL AMERICAN REMAKES MOVIES - Fithratullah, Muhammad; Kasih, Elisabeth Ngestirosa Endang Woro; Al Falaq, Janata Shoji; Fadel, Muhammad (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2024)
This study explores the transformation of values in transnational remake movies, focusing on their popularity and the incorporation of new elements to suit target audience preferences. An analysis of The Lake House, a remake of the Korean film Il Mare, reveals shifts in values and the integration of American cultural aspects. These changes stem from audience demands, business considerations, and Hollywood's global influence. Remakes require more than simply reproducing original content; they involve capturing cultural nuances from both versions. Utilizing Hall's representation approach and qualitative methods, the study assesses transnational remakes and their conveyed values. The research identifies shifts from South Korean values to those of the American target market, such as the transition from interdependence to self-reliance and a preference for directness, assertion, and rationality. The American film industry should carefully evaluate the suitability of movies for its audiences, recognizing changes in scenes and messages. The establishment of American values in remakes is influenced by the success of original films and their formulas. As transnational products, movies must be repackaged for target audiences. The industry faces complex processes to align the values of popular films with audience tastes while maintaining the essence of original works.